2019
DOI: 10.1515/itit-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Design of a microgrid local energy market on a blockchain-based information system

Abstract: In this paper, we propose a model-based system architecture for an interoperable blockchain-based local energy market for prosumers in a residential microgrid setting. Based on the Smart Grid Architecture Model our analysis deduced 21 organizational, informational, technical and blockchain requirements for a local energy market and its underlying information system. These are evaluated in the Landau Microgrid case study. We derive, that a clear value proposition for the key stakeholders, standardization of dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…It was concluded that introducing LEM provides an efficient mechanism to reduce costs. An enhanced security management system for LEM is also proposed in [78], where model-based system architecture was designed for an interoperable blockchain-based LEM for prosumers in a residential microgrid setting. It shows the confidentiality and integrity required for energy trading to sustain continued energy supply and sales, the ability to track energy sources during energy generation and energy dispatch so that renewable energies are separately identified from non-renewables, and access for customers to energy data transaction details so that the type of energy provisioned to their premises is known.…”
Section: Impact Of Lem On Microgrids and Possibility To Improve By In...mentioning
confidence: 99%
“…It was concluded that introducing LEM provides an efficient mechanism to reduce costs. An enhanced security management system for LEM is also proposed in [78], where model-based system architecture was designed for an interoperable blockchain-based LEM for prosumers in a residential microgrid setting. It shows the confidentiality and integrity required for energy trading to sustain continued energy supply and sales, the ability to track energy sources during energy generation and energy dispatch so that renewable energies are separately identified from non-renewables, and access for customers to energy data transaction details so that the type of energy provisioned to their premises is known.…”
Section: Impact Of Lem On Microgrids and Possibility To Improve By In...mentioning
confidence: 99%
“…Permissioned (also called private) blockchains were implemented and described, but lacked details about how the community was self-governed [17,47]. In [48], the authors recommended permissioned blockchains for local energy markets where participants seem to be limited to trading without participation in the governance. Another blockchain based local energy market required a central utility to register participants and assigns authority to prosumers with a genuine PV for block validation [49,50].…”
Section: Review Of the Regulatory Framework Regarding Legal Contracts...mentioning
confidence: 99%
“…The purpose of this consensus mechanism is to secure a transaction history and at the same time to ensure the governance of the decentralized system over as many (anonymous) participants as possible. Due to the high energy demand of the proofof-work mechanism, this consensus mechanism is not suitable for applications targeting energy efficiency [48].…”
Section: Finding a Consensusmentioning
confidence: 99%
“…They are progressively using energy management systems and thinking about onsite resources such as renewable energy and energy storage. Many people are taking part in current utility programs to meet their energy management objectives, and some see further potential in the more participatory electric utility and market programs [19].…”
Section: State Of Art Of the Smart Energy Management Systems 41 Introductionmentioning
confidence: 99%